“I Learnt Much About…” the Impact of Cooperative Interreligious Education - Danner, Sonja 20./21. Jh. (Religions, 2024)
Population growth in Austria means that school classes—including those in apprenticeship training—are no longer homogeneous. Apprentices, too, often come from different cultural backgrounds and therefore belong to different religions and worldviews, which makes the classes “multi” in every respect. This can lead to encounters in their everyday working life that are not always smooth because they are accompanied by prejudices and misunderstandings. Can cooperative religious education based on didactics of facilitation and TCI help to gain new insights into religions/worldviews and thus reinforce social cohesion? It has been shown that cooperative religious education gives pupils an insight into religious communities to which they themselves do not belong but does not give much concrete knowledge. It creates an awareness of being different without devaluation and the importance of dialogue that leads to a better mutual understanding and consequently to an awareness of one’s own prejudices and judgements towards others. It cannot be said that the attitudes towards religions/denominations/worldviews that were foreign to the pupils have changed with KORU but effects on social interaction are recognisable. The evaluation according to Philipp Mayring (content analysis) was carried out using a triangulation of data: Observation of religious education lessons, lesson preparations and interviews with the participating teachers and two group interviews with students and their written reflections.